2014
DOI: 10.3347/kjp.2014.52.3.273
|View full text |Cite
|
Sign up to set email alerts
|

Increased Intestinal Epithelial Cell Turnover and Intestinal Motility in Gymnophalloides seoi-Infected C57BL/6 Mice

Abstract: The changing patterns of goblet cell hyperplasia, intestinal epithelial cell turnover, and intestinal motility were studied in ICR and C57BL/6 mice infected with Gymnophalloides seoi (Digenea: Gymnophallidae). Whereas ICR mice retained G. seoi worms until day 7 post-infection (PI), C57BL/6 mice showed a rapid worm expulsion within day 3 PI. Immunosuppression with Depo-Medrol significantly delayed the worm expulsion in C57BL/6 mice. Goblet cell counts were increased in both strains of mice, peaking at day 1 PI … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…It has been shown that immune-mediated expulsion of intestinal helminths can involve the interplay between CD4+ T cells and the gut epithelium [ 1 – 3 ]. Increased epithelial cell turnover is a potential dislodging mechanism that may affect the steadiness of worms in their intestinal microhabitat and, therefore, result in parasite clearance [ 4 8 ]. However, the effectiveness of this mechanism strongly depends on the host-parasite system, since they may be affected by diverse parasite evasion strategies that render the host susceptible [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that immune-mediated expulsion of intestinal helminths can involve the interplay between CD4+ T cells and the gut epithelium [ 1 – 3 ]. Increased epithelial cell turnover is a potential dislodging mechanism that may affect the steadiness of worms in their intestinal microhabitat and, therefore, result in parasite clearance [ 4 8 ]. However, the effectiveness of this mechanism strongly depends on the host-parasite system, since they may be affected by diverse parasite evasion strategies that render the host susceptible [ 3 ].…”
Section: Introductionmentioning
confidence: 99%